Immunolocalization of dynein, dynactin, and kinesin in the cerebral tissue as a possible supplemental diagnostic tool for traumatic brain injury in postmortem examination - Olczak, Mieszko; Poniatowski, Łukasz; Kwiatkowska, Magdalena; Samojłowicz, Dorota; Tarka, Sylwia; Wierzba-Bobrowicz, Teresa (Folia Neuropathologica, 2019)
Traumatic brain injury (TBI) is characterized by various micro- and macrostructural neuropathological changes which can be identified in the light microscope examination. The most common pathophenotype of TBI visualized in postmortem neuropathological assessment includes neuron injury with involvement of all of its structural regions followed by its progressive degeneration defined as traumatic axonal injury (TAI). This is directly related with disruption of the axolemmal cytoskeletal network architecture resulting in breakdown, dissolution and accumulation of a number of neuronal proteins. Regarding the availability and progress in the development of specific antibodies against neuronal proteins, their usage is restricted due to low specificity for injured axons in the pathomechanism of TBI followed by TAI. Taking this into account with relation to expanding the role of axonal cytoskeleton and its based biomarkers we have presented a study documenting neuropathological features concerning the expression of dynein (DNAH9), dynactin (DCTN1) and kinesin (KIF5B) in the brain specimens obtained during forensic autopsies from TBI victims. The study was carried out using cases (n = 21) of severe head injury suspected to be the cause of death and control cases (n = 17) of sudden death in the mechanism of cardiopulmonary failure along with a positive control case which died after suicidal gunshot injury. In our study, we documented that DNAH9, DCTN1, and KIF5B staining should be considered as a supplemental diagnostic tool for TBI in postmortem neuropathological examination and forensic autopsy. This additional motor protein immunohistochemical staining procedure could be useful in the evaluation of lesions that may remain undiagnosed during a routine examination and aid in more accurate identification of TBI followed by TAI.